The moralizing discourse of Justo Arosemena through the catechism - Romero Colmenares, Rosalina Rosalba (Espergesia, 2025)
The article presented the bibliographical documentation used as the basis for the doctoral research entitled Justo Arosemena, Discourse and Identity: A Linguistic Study. The study included, among other documents, an analysis of the catechism-type work Principles of Political Morality Written in a Catechism by Panamanian lawyer and politician Justo Arosemena, a work that we analyze in this article. Arosemena stood out during the 19th century for his role in the quest for independence and the construction of the Panamanian nation. The article was structured in three parts: the first offered a historical documentary compilation to provide a preliminary context for the 19th century in the Isthmus of Panama; the second presented a bibliographic review of the theory used, followed by the literature of the documents analyzed, which facilitated the inquiry and deepening of the study. The third part included the conclusion and bibliography. The methodology used was based on a linguistic corpus that was codified to facilitate the study. The value of the article lay in the fact that it is the first time that a critical discourse analysis has been carried out using the technique of compiling a vast corpus of selected writings by Justo Arosemena, utilizing linguistic strategies, which allowed for an in-depth assessment of the production chosen for study.